Predicting Future Halal Tourist Behavior: Incorporating Holistic Tourist Experience and Virtual Reality Experience - Tintin Suhaeni; Anthony Brien; Tomy Andrianto; Maryam Taha Mannaa (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
This study evaluates the role of experience visiting tourism destination in person as well as via VR in predicting Muslim tourist behavioral intention during the COVID-19 pandemic. The data were gathered using an online survey from 291 Muslim tourists from Muslim majority countries as well as non-Muslim majority countries. Partial least square was utilized to assess the behavioral intention model. The result shows that behavioral intention of tourists from Muslim countries is driven by experience quality and experience via VR, while tourists from non-Muslim countries are driven by experience with VR. Further, halal experience is not a significant factor in driving behavioral intention for halal tourists from both Muslim and non- Muslim countries.